Series Images as A Stimulation of Language Ability for Left Brain Development in Early Children - Lestari, Nyamini Ika; Latif, Nur Fauziah (Proceedings International Conference on Education Innovation and Social Science, 2023)
It is important to provide proper stimulation and support for left brain development at every stage of development. Media picture series can be an effective means to stimulate the development of the left brain. Left brain development is critical for language processing, logical reasoning, and analytical thinking. Media picture series can play an important role in stimulating the development of the left brain. Through mastery of language, reading and writing skills, mathematical abilities, logical reasoning, and critical thinking, visual media can optimally support the development of the left brain. It is important to provide engaging and educational visual media and create opportunities for children to interact and discuss content to strengthen their left brain development. It is important to provide a variety of interesting and varied images and interact and discuss with children about these images to strengthen understanding and development of the right brain . to improve speaking ability is to use serial pictures. Picture series is a series of pictures arranged sequentially to tell a story or concept. This study aims to explore the use of serial images in improving speaking skills. The method used is an experiment involving a group of participants who have varying levels of speaking ability. The results of the study show that the use of serial images can be effective in improving speaking skills. Participants involved in the experiment showed a significant increase in their ability to express ideas and speak fluently after using picture series as a tool. In addition, the use of picture series can also increase the creativity and imagination of participants. By looking at the pictures arranged sequentially, participants can develop a story or concept in a better and more structured way. This research makes an important contribution in the field of education and communication. The use of serial pictures can be an effective alternative in improving speaking skills, especially for those who have difficulty expressing ideas verbally.